2003
DOI: 10.1359/jbmr.2003.18.5.807
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Loading Stimulates Dentin Matrix Protein 1 (DMP1) Expression in Osteocytes In Vivo

Abstract: Dentin matrix protein 1 (DMP1) was originally postulated to be dentin specific. Further analysis showed that DMP1 is also expressed in mature cartilage and bone. In bone tissue, DMP1 is expressed predominantly in late osteoblasts and osteocytes. DMP1 belongs to the SIBLING (Small Integrin Binding Ligand N-linked Glycoprotein) family of cellular matrix proteins that also includes osteopontin, bone sialoprotein, dentin sialophosphoprotein, and others. In this study, we examined the effect of mechanical loading o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
114
0
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(129 citation statements)
references
References 50 publications
(129 reference statements)
9
114
0
6
Order By: Relevance
“…Immunohistochemical studies have demonstrated that signals for PHEX protein are stronger in osteocytes than in osteoblasts and localized predominantly on the plasma membrane (35). Likewise, DMP1 in bone is more highly expressed in osteocytes than in osteoblasts (36,37). This coincidental localization of DMP1 and PHEX protein in osteocytes and osteoblasts strengthens the possibility that PHEX protein may be the proteinase involved in the processing of DMP1.…”
Section: Discussionmentioning
confidence: 76%
“…Immunohistochemical studies have demonstrated that signals for PHEX protein are stronger in osteocytes than in osteoblasts and localized predominantly on the plasma membrane (35). Likewise, DMP1 in bone is more highly expressed in osteocytes than in osteoblasts (36,37). This coincidental localization of DMP1 and PHEX protein in osteocytes and osteoblasts strengthens the possibility that PHEX protein may be the proteinase involved in the processing of DMP1.…”
Section: Discussionmentioning
confidence: 76%
“…In the present study, expression of DMP1 in incisor PDL was enhanced progressively within the PDL region with age in dKO vs. WT mice. DMP1 is suggested to be a mechanosensor, with increased expression in mechanically loaded osteocytes (Gluhak-Heinrich et al, 2003). It is important to note that rodent incisors are continuously growing.…”
Section: Slrps Regulate Collagen Fibrillogenesis and Periodontal Homementioning
confidence: 99%
“…As well, unloading causes osteopontin expression in osteocytes (Gross et al, 2005). Dentin matrix protein (DMP1), which is a secreted matrix protein expressed in late osteoblasts and osteocytes, has been shown to increase in osteocytes after tooth movement in the jaw (Gluhak-Heinrich et al, 2003).…”
Section: Mechanosensitive Bone Cellsmentioning
confidence: 99%